Using a peak flow meter to assess severity of exacerbation in patients suffering from chronic obstructive pulmonary disease: a prospective observational study - Sreekumar, Arunkumar; Kiran Kumar (International Journal of Research in Medical Sciences, 2023)
Background: Chronic obstructive pulmonary disease (COPD) is an important and dangerous public health concern, and deaths due to it has become the leading cause of mortality in several countries. Exacerbations of the disease are very common and is frequently responsible for progressive decline in lung function, quality of life and ultimately death. Through this study, we hypothesize whether estimating peak expiratory flow rate (PEFR) using a simple peak flowmeter could help in early prediction of the intensity and severity of exacerbations of COPD. Methods: This study was conducted amongst 100 patients, at Amrita Institute of Medical Sciences, Kochi, Kerala, who were diagnosed with COPD, based on GOLD criteria and respective pulmonary function tests. Their PEFR and oxygen saturation values were recorded during their routine clinic visits and during an exacerbation episode and results were analyzed. Results: Out of 100 patients, 91 were males and 9 were female patients, with a mean age of 64.4 years and commonest age affected is 55 years. Average duration of COPD amongst the study participants ranged from 4 to 11 years with a mean of 7.19 years. PEFR was graded into 3 zones based on guidelines and measurements noted. Of the 76 male patients with 80-100% PEFR recordings, 10 (13.15%) had a drop to 50-80% PEFR and 66 (86.85%) of them dropped to <50% PEFR reading during an exacerbation. For the female subjects, of the 9 patients with 80-100% of expected PEFR, 3 (33.33%) had dropped to 50-80% and 6 (66.69%) had dropped to <50% of PEFR reading. SpO2 had significant change at exacerbations as compared during normal phase dropping with mean of 94.82 to 81.3 which was statistically significant across age and gender. Wilcoxon signed rank test was done to quantify statistical change showed z score of -9.138 with p<0.0001, which was significant across age and gender groups. Conclusions: As a simple, inexpensive tool, peak flowmeter could be useful for bedside monitoring of severity of exacerbation of COPD. This could be vital for early detection and appropriate medical intervention.